ANALISIS SARANA DAN PRASARANA PENDIDIKAN PADA PROGRAM KEAHLIAN AKUNTANSI DI SMK NEGERI 1 KABUPATEN SANGGAU - Liliani, Fransiska; Sumartono, Bambang Genjik; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this thesis is "Analysis of Educational Facilities and Infrastructure on Accounting Skills Program at The SMK Negeri 1 Sanggau Regencyâ€. The purposes of this research are first is to determine the availability of educational facilities and infrastructure on the Accounting Skills Program. Second is to study the feasibility of educational facilities and infrastructure in the Accounting Skills Program.The research method was used is descriptive qualitative study. The data sources of this research were the principal, the facilities and infrastructure deputy, the administrator of accounting laboratory and the library's manager.Data collected of this study were obtained from observations, interviews and documentation of educational facilities and infrastructure at SMK Negeri 1 Sanggau which were include furniture, educational media, educational equipment and other equipment.The data of facilities and infrastructure which are obtained then compared with the standards in Permendikbud No. 34 of 2018 concerning Facilities and Infrastructure Standards for Vocational High Schools / Madrasah Aliyah Vocational Schools (SMK / MAK).The results study showed that the availability of educational infrastructure at SMK 1 Sanggau was adequate, but if looked deeper there were several aspects for the facilities that were not yet feasible.The feasibility of educational infrasructure at SMK 1 sanggauSanggau in terms of the minimum broad aspects based on the Permendikbud No. 34 of 2018, there were 5 infrastructures that were suitable to be used and 2 infrastructures which were not yet suitable to be used.Â Keywords: Facilities and Infrastructure of Accounting EducationÂ